2015
DOI: 10.1002/pat.3497
|View full text |Cite
|
Sign up to set email alerts
|

The influence of multiple modified MMT on the thermal and fire behavior of poly (lactic acid) nanocomposites

Abstract: This work reported the preparation and physical properties of biodegradable nanocomposites fabricated using polylactic acid (PLA) and multiple organic modified montmorillonite (MMT). In order to improve the chemical compatibility between PLA and Na-MMT, the surface of Na-MMT was first organically modified by cetyl trimethyl ammonium bromide (CTAB) and resorcinol bis(diphenyl phosphate) (RDP) using ion-exchange and adsorption technique. Both Fourier transform infrared and X-ray diffraction (XRD) results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…As can be seen in Figure and Table , the primary (001) diffraction peak of neat OMMT is observed at 3.4°, which corresponds to an interlayer spacing of 2.6 nm. In the X‐ray diffraction pattern of PLLA‐1 sample, the (001) characteristic peak of OMMT is smaller than that of neat OMMT and corresponds to an interlayer spacing of 3.6 nm, indicating that OMMT nanoparticles are highly intercalated and exfoliated and the molecular chains of PLLA are successfully inserted and well dispersed in the OMMT galleries . Moreover, with increasing OMMT concentration, the (001) characteristic peak of nanocomposites becomes stronger but the interlayer spacing changes little, which indicates that there is still a finest intercalated and exfoliated structure of OMMT in the high OMMT concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen in Figure and Table , the primary (001) diffraction peak of neat OMMT is observed at 3.4°, which corresponds to an interlayer spacing of 2.6 nm. In the X‐ray diffraction pattern of PLLA‐1 sample, the (001) characteristic peak of OMMT is smaller than that of neat OMMT and corresponds to an interlayer spacing of 3.6 nm, indicating that OMMT nanoparticles are highly intercalated and exfoliated and the molecular chains of PLLA are successfully inserted and well dispersed in the OMMT galleries . Moreover, with increasing OMMT concentration, the (001) characteristic peak of nanocomposites becomes stronger but the interlayer spacing changes little, which indicates that there is still a finest intercalated and exfoliated structure of OMMT in the high OMMT concentration.…”
Section: Resultsmentioning
confidence: 99%
“…In the X-ray diffraction pattern of PLLA-1 sample, the (001) characteristic peak of OMMT is smaller than that of neat OMMT and corresponds to an interlayer spacing of 3.6 nm, indicating that OMMT nanoparticles are highly intercalated and exfoliated and the molecular chains of PLLA are successfully inserted and well dispersed in the OMMT galleries. 25 Moreover, with increasing OMMT concentration, the (001) characteristic peak of nanocomposites becomes stronger but the interlayer spacing changes little, which indicates that there is still a finest intercalated and exfoliated structure of OMMT in the high OMMT concentration. The result shows that the ERE has good mixing dispersion effect of promoting the intercalation and exfoliation of OMMT in the preparation of polymer nanocomposites.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…In recent years, polymer/inorganic hybrid nanoparticles are prevail among academic research, which combine the properties of both components and can provide unique and tunable properties. Nano‐sized fillers, such as carbon black and carbon nanotubes were used to modify PLA. Incorporation of nano‐sized particles, especially silica particles, into PLA can improve its melt behavior, mechanical properties, and thermal stability …”
Section: Introductionmentioning
confidence: 99%
“…This suggested that the migrated NATP on the burning surface was crosslinked by a large amount of char produced via the interaction between RDP and PLA. Liu et al [62] used double modified pristine MMT to improve the fire retardancy of PLA. First the surface of the sodium-MMT was organically modified by cetyl trimethyl ammonium bromide then by resorcinol bis(diphenyl phosphate) via ion-exchange and adsorption, respectively.…”
Section: Poly(lactic Acid) With Nanofiller As Flame Retardantmentioning
confidence: 99%